A dual oral intestinal film for pulsatile release of a mood stabilizing agent in the treatment of schizoaffective disorder - Hoosain, Famida Ghulam (My University, 2016)
Oral drug delivery is acknowledged by many as the idyllic method of drug delivery due to its versatility and convenience of administration. Nevertheless, the bioavailability of drugs delivered via the oral route remains disputed. Classically, conventional marketed drug delivery systems release drugs in inconstant and unpredictable manners, leading to sub-therapeutic and in some cases toxic drug doses. Consequently, patient compliance is compromised, in turn having an effect on the success of the therapeutic intervention in question. One such limitation occurs in the treatment of Schizophrenia, with patients unable to comply with treatment due to multiple administration requirements. Sulpiride, an antipsychotic agent, displays notable efficiency in reducing both positive and negative symptoms of Schizophrenia. However, sulpiride has a low bioavailability and thus therapy requires the use of large doses, and hence multiple administrations. In addition, a large percentage of Schizophrenic patients present with concomitant mood disorders, namely ‘Schizoaffective’ disorder, which further necessitates the use of mood stabilizing agents. As a result, patients end up with a huge pill burden and are unable to comply with therapy and this leads to reduced clinical outcomes. A dual layered, xerogel-bioadhesive intestinal patch drug delivery system (ODLS) was thus designed, formulated, and evaluated for the site-specific delivery of two bioactives in the treatment of Schizophrenia with concomitant mood disorders in a time controlled-idiosyncratic manner. Ultimately easing compliance to complicated treatment regimens, enhancing bioavailability and improving patient compliance. The ODLS essentially comprises of a bi-layered tablet, layer one comprised of a sustained release semi-interpenetrating polymer network (s-IPN) xerogel and a layer two of embedded pulsatile release bioadhesive intestinal patches, with the system as a whole enteric coated for protection. Intestinal patches encompassed in layer two are fabricated of a backing layer, a drug loaded layer, a mucoadhesive layer, and a mucus cleaving layer. The ODLS employs a combination of sustained and pulsatile drug release mechanisms, in addition to intestinal retentive mechanisms. Furthermore, the system physically protects the drug delivery system from acidic or proteolytic degradation within the human gastro-intestinal tract. The present study utilized the use of bioadhesion for site-specific and gastro retentive drug delivery, with crosslinking being employed for rate-modulated drug delivery. Sulpiride and sodium valproate were selected as model drugs for the sustained release xerogel layer and the pulsatile bioadhesive patch layer respectively in this study as sulpiride is an antipsychotic with low bioavailability yet good antipsychotic activity and sodium valproate is the mainstay drug treatment for mood disorders in schizophrenia. Therefore, sulpiride would profit from the sustained release as it would improve bioavailability and hence patient compliance, whereas sodium valproate would benefit from the pulsatile release so as to avoid the well-known resistance to therapy due to prolonged exposure to drug. Thus these drugs would gain benefit from the site-specific controlled drug delivery offered by the ODLS. The primary aim of the sustained release s-IPN xerogel was to ensure delayed release of drug over 24 hours thus decreasing the need for multiple administrations and to maintain a steady state drug concentration. Film casting, a versatile technique was utilized in the fabrication of polymeric films to develop the bioadhesive intestinal patches. Preliminary in vitro investigations led to identification of a combination of polymers and crosslinking agent best suited to develop the system. A central composite design was employed for system optimization. The xerogel layer demonstrated that zero-order drug release was achieved after the crosslinking procedure. Delayed drug release fundamentally decreases the number of doses required daily and thus patient compliance and clinical efficacy is improved. The pulsatile release layer displayed distinct triphasic drug release after assembly of the intestinal patches, pulsatile release of drugs fundamentally reduced resistance to drug therapy as well as reducing pill burden. Furthermore, in vitro analysis of the ODLS showed that the xerogel layer behaved superiorly in terms of controlling drug delivery in a site-specific and prolonged fashion in comparison to a marketed gold standard. There exists no gold standard for pulsatile delivery of sodium valproate hence the pulsatile layer was tested against the marketed standard administered as a single dose. In vitro findings were substantiated by in vivo analysis in a white pig model. Results indicated that the systemic bioavailability of sulpiride was higher than the gold standard and drug release was prolonged in a zero-order fashion over 24 hours. Sodium valproate released in a triphasic manner over 24 hours thus reducing the risk of treatment resistance and decreased pill burden. To summarize, the ODLS was able to overcome the many challenges associated with oral drug delivery in schizoaffective disorder, by simplification of complicated treatment regimens, and hence improving bioavailability of drug delivery orally. The benefits associated with oral drug delivery have evidently been exploited by the present study, producing a versatile drug delivery system which can successfully deliver two bioactives simultaneously via individualistic release patterns, thus treating both conditions with a single oral dosage form with a single daily administration.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2016
Keywords: Psychotic Disorders; Drug Delivery Systems